A Ca2+/calmodulin-dependent protein kinase, CaM kinase-Gr, expressed after transformation of primary human B lymphocytes by Epstein-Barr virus (EBV) is induced by the EBV oncogene LMP1. - Mosialos, G (1994)
CaM kinase-Gr is a multifunctional Ca2+/calmodulin-dependent protein kinase which is enriched in neurons and T lymphocytes. The kinase is absent from primary human B lymphocytes but is expressed in Epstein-Barr virus (EBV)-transformed B-lymphoblastoid cell lines, suggesting that expression of the kinase can be upregulated by an EBV gene product(s). We investigated the basis of CaM kinase-Gr expression in EBV-transformed cells and the mechanisms that regulate its activity therein by using an EBV-negative Burkitt lymphoma cell line, BJAB, and BJAB cells converted to expression of individual EBV proteins by single-gene transfer. CaM kinase-Gr expression was upregulated in BJAB cells by EBV latent-infection membrane protein 1 (LMP1) but not by LMP2A or by nuclear proteins EBNA1, EBNA2, EBNA3A, and EBNA3C. In LMP1-converted BJAB cells, the kinase was functional and was dramatically activated upon cross-linking of surface immunoglobulin M. Overlapping cDNA clones that encode human CaM kinase-Gr were sequenced, revealing 81% amino acid identity between the rat and human proteins. Transfection of BJAB cells with an expression construct for the human enzyme resulted in a functional kinase which was shown by epitope tagging to localize primarily to cytoplasmic and perinuclear structures. Induction of CaM kinase-Gr expression by LMP1 provides the first example of a Ca2+/calmodulin-dependent protein kinase upregulated by a viral protein. In view of the key role played by LMP1 in B-lymphocyte immortalization by EBV, these findings implicate CaM kinase-Gr as a potential mediator of B-lymphocyte growth transformation.